Assessment of long-range oriented source and oxidative potential on the South-west shoreline, Korea: Molecular marker receptor models during shipborne measurements. (15th July 2021) - Oh, Sea-Ho; Song, Myoungki; Schauer, James J.; Shon, Zang-Ho; Bae, Min-Suk
Abstract: In order to determine the quantitative contributions of PM2.5 on the South-west shoreline of Korea, filter based samplings were conducted in the summertime of 2017 and 2018 (total 32 days) via shipborne measurements using both a high volume and middle volume air sampler. Water-soluble organic carbon, water-soluble ions, organic carbon and elemental carbon, elemental species, and organic molecular markers by Liquid Chromatography–tandem Mass Spectrometry were utilized to characterize the collected substrates. The current study investigates the (1) chemical characteristics of PM2.5, (2) source apportionment using positive matrix factorization (PMF), and (3) relationship between sources and the dithiothreitol (DTT) assay during the two sampling periods. A mean PM2.5 concentration of 19.3 μg/m 3 was observed along the entire sampling route. The ratio of water-soluble to organic carbon implies that secondary aerosol formation is dominant. The result of methanesulfonic acid (MSA) suggests the contribution of a marine-oriented biogenic source of PM2.5 . The PMF source apportionment model showed six source categories with reasonably stable profiles: 1) sulfate-rich, 2) MSA-rich, 3) nitrate-rich, 4) secondary organic, 5) continental, and 6) biomass burning sources. The PMF showed three strong events (i.e., long-range transport, mixed (ocean and long-range stay), and domestic origin events) in the contributions of sources, as well as a dependence on wind transport. Higher associations with DTT oxidative potential normalized to PM2.5 mass concentration (DTT–OPm ) related to long-range transport, hence, confirming the impacts of the highest intrinsic oxidative potential. Graphical abstract: Image 1 Highlights: Relationship between PM2.5 source apportionment and dithiothreitol assay. Higher intrinsic oxidation potential for the long-range migrating particles. Harmfulness and hazards of aged PM2.5 in Asian outflow.